Interpretation and Physical Meaning of Kinetic Parameters Obtained from Isoconversional Kinetic Analysis of Polymers - Sbirrazzuoli, Nicolas (Polymers (Basel), 2020)
Several successful examples—where physically sounded kinetic information was obtained from thermoanalytical data in different application fields, such as polymerization of thermosetting resins, biobased polymers and nanocomposites, crystallization and glass transition of semi-crystalline polymers and their nanocomposites—are here presented and discussed. It is explained how the kinetic parameters obtained from advanced isoconversional methods can be interpreted in terms of reaction mechanisms or changes in the rate-limiting step of the overall process, in the case of complex chemical reactions or complex physical transitions, and how these parameters can be used to extract model-fitting parameters.